GADAI DALAM PERSEPEKTIF HUKUM EKONOMI ISLAM - Adanan Murroh Nasution (Institut agama islam negeri Padangsidimpuan, 2019)
Pawn is to make economic assets as collateral for loans. Jumhur scholars have a pillar of pawn. There are four parties, namely those who are committed (rahin and murtahin), mortgaged goods (marhun), debt (marhunbih) and sighat. However according to hanafiyah rukun pawn only one is sighat, apart from sighat according to hanafiyah, it is not included as a pawn requirement. Because the essence of a transaction according to hanafiyah is on the consent and qabul. While the conditions for pawning are, those involved in pawning transactions must be legal persons. in the form of valuable assets and can be handed over to the pawned party at the time of the contract. Debt in this transaction remains a debt that does not add up. Highlights used in the pawn contract may be in oral or written form.The scholars differed in regard to the law on the use of collateral. The majority of scholars do not allow them to make use of guaranteed goods because the goods and benefits are the property of their owners. According to some other ulama, anmarhun can use collateral if he has obtained permission from the owner. Meanwhile, according to Imam Ahmad and Ishaq, if the collateral is in the form of a vehicle that can be used or livestock that can be ridden and milked, the recipient of the pawn may use the collateral as a substitute for the cost of maintaining the collateral. Sharia pawnshop is the right solution to obtain funds easily and quickly Sharia pawnshop is free from usury whose operation is in accordance with the fatwa of the National Sharia Council (DSN).